2020
DOI: 10.1152/jn.00069.2020
|View full text |Cite
|
Sign up to set email alerts
|

Cortical processing of chemosensory and hedonic features of taste in active licking mice

Abstract: Relatively little information is available on the neural dynamics of taste processing in the mouse gustatory cortex (GC). In this study we investigate how the GC encodes chemosensory and palatability features of a wide panel of gustatory stimuli when actively sampled through licking. Our results show that GC neurons broadly encode basic taste qualities but also process taste hedonics and licking information in a temporally dynamic manner.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 63 publications
1
34
0
Order By: Relevance
“…A continuous trehalose administration over an extended period may mimic long-term nutrient deficiency for neurons, and one may speculate that neurons will try to save energy and reduce their activity. We assume that antinociceptive effects and the in vivo sedation-like behavior reflect sedation-like effects on excitatory neurons, based on previous studies using in vivo electrophysiologic recordings in behaving mice [ 61 , 62 , 63 ]. However, we did not directly study cortical activity under trehalose.…”
Section: Discussionmentioning
confidence: 99%
“…A continuous trehalose administration over an extended period may mimic long-term nutrient deficiency for neurons, and one may speculate that neurons will try to save energy and reduce their activity. We assume that antinociceptive effects and the in vivo sedation-like behavior reflect sedation-like effects on excitatory neurons, based on previous studies using in vivo electrophysiologic recordings in behaving mice [ 61 , 62 , 63 ]. However, we did not directly study cortical activity under trehalose.…”
Section: Discussionmentioning
confidence: 99%
“…While it is important to highlight that taste-responsive neurons in the gustatory cortex are often multimodal (see the section 4), these studies showed that neurons in the gustatory cortex represent the identity and hedonic value of taste stimuli. Neurophysiological data obtained from extracellular recordings in anaesthetized and alert rodents highlight the presence of both narrowly-tuned neurons (those modulated by one taste quality) and broadly-tuned neurons (those modulated by multiple taste qualities) (Yamamoto et al, 1981 ; Kosar et al, 1986 ; Ogawa et al, 1992 ; Katz et al, 2001 ; Stapleton et al, 2006 ; Jezzini et al, 2013 ; Levitan et al, 2019 ; Bouaichi and Vincis, 2020 ; Dikecligil et al, 2020 ), with the latter being the majority in awake conditions (Katz et al, 2001 ; Stapleton et al, 2006 ; Samuelsen et al, 2012 , 2013 ; Jezzini et al, 2013 ; Levitan et al, 2019 ; Bouaichi and Vincis, 2020 ). Studies in alert rodents, receiving taste stimuli either via an intraoral cannula (IOC) or by licking a spout, emphasized the importance of the temporal dynamics of taste-evoked activity.…”
Section: Unimodal Processingmentioning
confidence: 99%
“…For example, the intraoral delivery of taste stimuli evokes different epochs in firing rates during the first 2.5 s. In this context, the neural activity first represents the presence (~0–250 ms), then the identity (~250–750 ms), and finally the hedonic value of taste stimuli (Katz et al, 2001 ; Fontanini and Katz, 2006 ; Jones et al, 2007 ; Grossman et al, 2008 ; Piette et al, 2012 ; Sadacca et al, 2012 ; Jezzini et al, 2013 ; Samuelsen et al, 2013 ; Levitan et al, 2019 ; Mukherjee et al, 2019 ). In addition, studies in which rodents lick a spout to receive taste stimuli revealed additional complex and rich temporal dynamics related to licking rhythmicity in the gustatory cortex (see the section 4) (Stapleton et al, 2006 ; Gutierrez et al, 2010 ; Bouaichi and Vincis, 2020 ).…”
Section: Unimodal Processingmentioning
confidence: 99%
See 2 more Smart Citations